CHARACTERISTICS OF DEVELOPING MORAL EDUCATION IN CHILDREN (World Bulletin of Social Sciences, 2022)
He considers spiritual and moral education to be an important factor in raising the young generation to become a mature person. The necessity of spiritual and moral education of these children, as well as its specific features, will be considered